Photocatalytic degradation of food dye by Fe3O4–TiO2 nanoparticles in presence of peroxymonosulfate: The effect of UV sources. Issue 3 (June 2017) - Zazouli, Mohammad Ali; Ghanbari, Farshid; Yousefi, Maryam; Madihi-Bidgoli, Soheila
Graphical abstract: Highlights: The photocatalytic activity of Fe3 O4 –TiO2 was evaluated in presence of PMS. Fe3 O4 –TiO2 exhibits a dual role for activation of PMS. Various UV sources were assessed for Fe3 O4 –TiO2 /PMS to degrade food dye. The contribution of sulfate and hydroxyl radicals was depended on UV source. Abstract: Food dyes are extensively used in food industry and their residual in aquatic environment makes environmental problems. In this study, F3 O4 -TiO2 nanoparticles (FTNs) were prepared and their characteristics were evaluated by X-ray powder diffraction (XRD), field emission scanning electron microscope (FESEM), vibrating sample magnetometer (VSM), Brunauer–Emmett–Teller (BET) specific surface area and energy dispersive spectroscopy (EDS). The catalytic activity of FTNs was tested for Brilliant Blue FCF decolorization in FTNs/UVA system in the presence of peroxymonosulfate (PMS) as electron acceptor. The results showed that 100% decolorization occurred under the condition of pH = 6.0, PMS = 2.0 mM, 0.8 g/L FTNs and 60 min reaction time. First-order kinetic was fitted for FTNs/UVA/PMS with rate constant of 0.059 min −1 . PMS exhibited a superiority compared to other electron acceptors (persulfate and hydrogen peroxide). FTNs maintained its activity in 4th cycle and showed a dual catalytic behavior; photocatalyst and PMS activation via Fe3 O4 . The effects of UV sources were investigated and the results indicated that UVC region and the use of LED (Light-emitting diode) accelerated the decolorization considerably. Compared to UVA, UVC increased hydroxyl radical contribution in degradation of the dye. Mineralization was also tested by total organic carbon and the order of mineralization follows: FTNs/UVA/PMS < FTNs/UVC/PMS ≤ FTNs/UVA-LED/PMS < FTNs/UVC-LED/PMS.